Steroidal glycosides from the Vietnamese cultivar Cordyline fruticosa "Fairchild red". (December 2021) - Nguyen, Duc Hung; Mitaine-Offer, Anne-Claire; Miyamoto, Tomofumi; Tanaka, Chiaki; Bellaye, Pierre-Simon; Collin, Bertrand; Chambin, Odile; Lacaille-Dubois, Marie-Aleth
Abstract: A phytochemical study of Cordyline fruticosa "Fairchild red" (Asparagaceae) from Vietnam, led to the isolation of fourteen steroidal glycosides, including twelve previously undescribed along with two known ones. Ten compounds were obtained by successive solid/liquid chromatographic methods from an aqueous-ethanolic extract of the roots, and four from the aerial parts. Their structures were elucidated mainly by spectroscopic analysis 2D NMR and mass spectroscopy (ESI-MS), as spirostanol glycosides, 5α-spirost-25(27)-ene-1β, 3β, 4α-triol 1- O -β-D-fucopyranoside, 5α-spirost-(25)27-ene-1β, 3β, 4α-triol 1- O -β-D-xylopyranoside, 5α-spirost-(25)27-ene-1β, 3β, 4α-triol 1- O -α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside, 5α-spirost-(25)27-ene-1β, 3β, 4α-triol 1- O -α-L-rhamnopyranosyl-(1 → 2)-(4- O -sulfo)-β-D-fucopyranoside, 5α-spirost-25(27)-ene-1β, 3β-diol 1- O -α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside, and 5α-spirost-25(27)-ene-1β, 3β-diol 1- O -α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranoside. Furostanol glycosides were also isolated as 26- O- β-D-glucopyranosyl-5α-furost-(25)27-ene-1β, 3β, 4α, 22α, 26-pentol 1- O- β-D-fucopyranoside, 26- O -β-D-glucopyranosyl-22α-methoxy-5α-furost-(25)27-ene-1β, 3β, 4α, 26-tetrol 1- O -β-D-fucopyranoside, 26- O- β-D-glucopyranosyl-5α-furost-(25)27-ene-1β, 3β, 22α, 26-tetrol 1- O- β-D-glucopyranoside, 26- O- β-D-glucopyranosyl-5α-furost-(25)27-ene-1β, 3β, 22α, 26-tetrol 1- O- α-L-rhamnopyranosyl-(1 → 2)-β-D-glucopyranoside, 26- O -β-D-glucopyranosyl-5α-furost-(25)27-ene-1β, 3β, 22α, 26-tetrol 1- O -α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside, and 26- O -β-D-glucopyranosyl-22α-methoxy-5α-furost-(25)27-ene-1β, 3β, 26-triol 1- O -α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside. All the isolated compounds were further evaluated for their cytotoxicity against 4T1 cell line, from a mouse mammary gland tissue, using MTS method. Graphical abstract: Fourteen steroidal glycosides, twelve undescribed, were isolated from Cordyline fruticosa (L.) A.Chev., cultivar "Fairchild red" (Asparagaceae). Their cytotoxicity was evaluated using MTS method. Image 1 Highlights: A phytochemical study of Cordyline fruticosa "Fairchild red" (Asparagaceae) from Vietnam was achieved. Fourteen steroidal glycosides were isolated, twelve previously undescribed and two known ones. Their structures were elucidated mainly by 2D NMR and mass spectrometry (ESI-MS). Six of them were spirostane-type glycosides and six of the furostane-type. Their cytotoxicity against a 4T1 cell line was evaluated.